1995
DOI: 10.1111/j.1432-1033.1995.0698h.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of (R)-2-hydroxyglutaryl-CoA Dehydratase from Acidaminococcus fermentans

Abstract: (R)-2-Hydroxyglutaryl-CoA dehydratase (HgdAB) from Acidaminococcus fermentans catalyses the reversible dehydration of its substrate to glutaconyl-CoA. The enzyme has to be activated by ATP, MgCl2, and Ti(III)citrate by an activator protein (HgdC) that is present in the organism at very low concentrations. Cell-free extracts of a recombinant Escherichia coli strain, in which hgdC was expressed, contained the activator with a specific activity of up to 45 U'/mg protein (1 U' is the amount of activator required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…Incubation with ferricyanide (10‐fold excess) led to denaturation of the protein. Exposure to air for 10 min had almost no effect on the spectroscopic behaviour nor on the activity of component D which clearly showed that it is by far not as oxygen sensitive as described earlier [5]. Incubation under oxic conditions for 24 h at 4 °C caused ≈ 30% loss of activity.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Incubation with ferricyanide (10‐fold excess) led to denaturation of the protein. Exposure to air for 10 min had almost no effect on the spectroscopic behaviour nor on the activity of component D which clearly showed that it is by far not as oxygen sensitive as described earlier [5]. Incubation under oxic conditions for 24 h at 4 °C caused ≈ 30% loss of activity.…”
Section: Resultssupporting
confidence: 50%
“…With a new purification method it was possible to purify 50 mg component D from 30 g wet cells of A. fermentans . Notably, the so isolated protein had a high specific activity of 9 U·mg −1 (15 s −1 ) compared to 5–6 U·mg −1 obtained previously [5]. Analysis of the enzyme gave 4.5 ± 0.3 nonheme iron and 3.5 ± 0.4 acid labile sulfur per heterodimer indicating the presence of a [4Fe−4S] cluster in component D. Upon heating of component D (2 mg·mL −1 , pH 7.0) at 75 °C for 20 min the protein precipitated and released 1.0 ± 0.1 flavin per heterodimer into the supernatant as determined by its absorbancies at 450 nm (ε = 11.3 m m −1 ·cm −1 ) and 370 nm (ε = 10.7 m m −1 ·cm −1 ) [32].…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…al. 1993;Müller and Buckel 1995) has sequence similarity to an open reading frame from E. coli designated "yijL" at 97 minutes on the chromosome (Burland et al 1995;Buckel 1996). Since 2-hydroxyglutarylCoA dehydratase is closely related to lactoyl-CoA dehydratase, we assumed that in E. coli, propionyl-CoA might indeed be degraded via the α-hydration of acryloyl-CoA.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of ( R )‐2‐hydroxyglutaryl‐CoA by acetyl‐CoA is mediated by glutaconate CoA‐transferase (Buckel et al ., 1981; Jacob et al ., 1997). The subsequent unusual dehydration of ( R )‐2‐hydroxyglutaryl‐CoA to glutaconyl‐CoA is catalysed by an flavin mononucleotide (FMN) and [4Fe–4S] cluster‐containing and ATP‐requiring two‐enzyme system (Buckel, 1980; Müller and Buckel, 1995). Finally, the decarboxylation of glutaconyl‐CoA completes this special pathway leading to the more general intermediate crotonyl‐CoA (eqn 1), which disproportionates to acetate, butyrate and molecular hydrogen (Härtel and Buckel, 1996b).…”
Section: Introductionmentioning
confidence: 99%